Transformasi Proyek Melalui Keajaiban Kecerdasan Buatan: Mengeksplorasi Potensi AI Dalam Project Management - Sulartopo Sulartopo; Siti Kholifah; Danang Danang; Joseph Teguh Santoso (Pusat Riset dan Inovasi Nasional, 2023)
The aim of this research is to discuss the potential of applying AI to improve PM activities and how project managers can objectively comment on issues of responsibility in taking action, accountability in decision making and the still important need for human reasoning. In the context of project management, AI has introduced new methods and techniques that enable project managers to work more quickly and efficiently. However, the unique complexity of projects can become a bottleneck in automating complex activities. The novelty of this research lies in its focus on exploring potential applications of artificial intelligence in project management. This study captures and discusses state-of-the-art research regarding AI applications in PM, providing strong evidence to highlight the benefits of AI techniques in providing intelligent solutions by learning from previous data even with incompleteness and uncertainty in an automated, efficient and reliable manner. The method used in this research is a literature review on the application of artificial intelligence in project management. Related research in the project management domain was collected to prepare a database for review. Then, the current use of AI in real-time projects and enterprises is evaluated for a more in-depth analysis. The research results show that AI has the potential to significantly improve project management processes in developing planning phases, conducting project charters, and integrated change control. The potential application of AI to enhance PM activities can objectively comment on issues of responsibility in taking action, accountability in decision making, and the critical need for human reasoning. AI is anticipated to categorize, measure and forecast potential risks associated with project performance and their relevant impacts, to carry out reliable investigations and analysis in advance regarding broad aspects of project management.